((2⁴)-³)/((4³)-²) Simplifique a expressão


URGENTE​


Resposta :

Resposta:

1

Explicação passo-a-passo:

Enunciado:

Simplifique a expressão

[tex]\frac{(2^{4} )^{-3} }{(4^{3} )^{-2} }[/tex]

Resolução:

[tex]\frac{(2^{4} )^{-3} }{(4^{3} )^{-2} } = \frac{2^{4*(-3)} }{4^{3*(-2)} } =\frac{2^{-12} }{4^{-6} } =\frac{2^{-12} }{(2^{2}) ^{-6} } =\frac{2^{-12} }{2^{-12} } =1[/tex]

Observação 1 → Potência de potência - mantém-se a base e multiplicam-se os expoentes.

Bom estudo

--------------------------

Sinais: multiplicação